The Application of Coopeartif Learning Model type STAD Assisted with Broad Transparent Diagrams, Alva board and Circle models to Improve Student Learning Outcomes on Broadly Simple Facets and Circles in Class VIA at SDN 15 Palu - Najmawati; Sudarman; Rizal, Muhammad (Jurnal Riset Pendidikan MIPA, 2017)
This research aims to describe the application of cooperative learning model type STAD assisted with broad transparent diagram, Alva board, and circle models to improve student learning outcomes on broadly simple facets and circles. This study was classroom action research (CAR) that refers to the design of Kemmis and Mc Taggart: planning, action, observation, and reflection and was conducted in two cycles. The results showed that the application of coopeartive learning model type STAD assisted with board transparant diagrams, alva board and circle model can improve student learning outcomes on broadly simpe facets and circle by using STAD steps: (1) teachers demonstrated a wide range of flat, simple rectangles, and circles by involving students using broad transparent diagram props, broadly alva-board models and circles; (2) the teacher conveied the scores / initial values of the students' abilities obtained from the daily test scores and the student's initial test; (3) the teacher established a group of students based on the academic ability of the high, moderate and low-ability students; (4) the teacher distributed LKS to the students done with group discussions, guiding students in turns doing LKS, randomly assigning student attendance number to do group presentation in front of class and giving reinforcement to student to the completion of LKS; (5) teacher gave quiz to the student individually and they do not allowed help each other; (6) the teacher guides the students to make summaries, direct and affirm the learning materials learned; (7) the teacher announced the achievement of the average score obtained by each group and rewards the group based on the group award criteria in a way- a certain way, and give an opportunity to that group who got a high average score to ask questions to a designated student outside his or her group and write the answer on the blackboard.